Evaluation on the interface characteristics, mechanism and performance of the dry modified SBS asphalt mixtures by multiscale methods - Zhang, Zijun; Yan, Wenda; Sun, Huadong; Ding, Yongling; Dong, Fuqiang (Scientific reports, 2025)
Dry modified Styrene–Butadiene–Styrene is an innovative asphalt modification method applied at the mixture level, offering many advantages in environmental-friendliness, efficiency, and convenience. However, its engineering application lacks comprehensive theoretical support. To address this gap and provide practical guidance for the production process of dry modified Styrene–Butadiene–Styrene asphalt mixtures, this study evaluates systematically the mixing conditions and investigates the microscopic mechanisms and performance impacts of dry modified Styrene–Butadiene–Styrene concerning modifier dosage, mixing temperature, mixing duration, and storage time. The research includes multiple scales: molecular simulations to analyze microscopic interactions, fluorescence microscopy and Fourier-transform infrared spectroscopy for mesoscopic observations, and asphalt mixture performance tests for macroscopic evaluations. Molecular dynamics simulation results indicate that when the dosage of dry modified SBS increases from 4 to 6%, the diffusivity improves by 20% and the interface strength increases by 32%. Microscopic tests results show that the optimal diffusion effect of SBS can be achieved when the mixing time of the mixture is 90 s. Macroscopic experiments provide the best preparation scheme for dry modified SBS: SBS dosage of 6%, mixing temperature of 180–185 °C, mixing time of 90 s, and storage time of 30 min. Under these conditions, the pavement performance of the dry modified SBS mixture can achieve optimal results.